Kryzys jako kategoria filozoficzna - Stachewicz, Krzysztof (Wydział Teologiczny, UAM, 2010)
The word "crisis" is one of the most popular words in public and political discourse, but also in private conversations. We talk about economical crisis, moral crisis, civilization crisis, crisis of science, of philosophy, crisis of man, of society, of democracy etc. We simply haye to ask whether in the human worid there exist things, processes, relations that are crisis-proof, which this notion cannot be referred to. It results in a strong semantic blur of this category. Negative senses of the word "crisis" connected with some deconstructions are mixed with positive ones which indicate possibilities of understanding and interpretation. Crisis can be a dramatically positive or tragically negatiye phenomenon. Crisis seems to be immanently inherent in the human condition and eo ipso in cultural structures built by man. Crisis has two components: a negative component - destruction of some structure or form, and a positive one - construction, building something new that takes into consideration and avoids the weaknesses of the old. All these distinctions and findings seem to play an important role in solving the crisis of marriage and family in the contemporary and (post)modem world.
Crisis as a Philosophical Category
Keywords: Crisis; Kryzys; Semantic blur; Rozmycie semantyczne; Positive and negative sense of crisis; Sens pozytywny i negatywny kryzysu; Crisis of marriage and family; Kryzys małżeństwa i rodziny